Low fetal fraction in cell‐free DNA testing is associated with adverse pregnancy outcome: Analysis of a subcohort of the TRIDENT‐2 study. (9th September 2021) - Becking, Ellis C.; Wirjosoekarto, Soetinah A. M.; Scheffer, Peter G.; Huiskes, Julia V. M.; Remmelink, Marinka J.; Sistermans, Erik A.; Bax, Caroline J.; Weiss, Janneke M.; Henneman, Lidewij; Bekker, Mireille N.
Abstract: Objectives: To assess the association between low fetal fraction (FF) in prenatal cell‐free DNA (cfDNA) testing and adverse pregnancy outcomes. Methods: We conducted a retrospective cohort study of participants of the TRIDENT‐2 study (Dutch nationwide government‐supported study offering cfDNA screening for fetal aneuploidies) who received a failed test result due to low FF (<4%) between April 2017 until February 2018. Outcome measures included pregnancy‐induced hypertension (PIH), pre‐eclampsia (PE), small for gestational age neonates (SGA), spontaneous preterm birth (sPTB), gestational diabetes mellitus (GDM), chromosomal aberrations, and congenital structural anomalies. Results: Test failure due to low FF occurred in 295 women (1.12% of tests performed). Information regarding pregnancy outcomes was available for 96.3% of these women. The incidence of PIH, PE, SGA, sPTB, and GDM was 11.2%, 4.1%, 7.3%, 5.1%, and 14.8%, respectively. The prevalence of chromosomal aberrations and congenital structural anomalies was 1.4% and 4.1%, respectively. Incidences of PIH, PE ≥ 34 weeks of gestation, GDM, and prevalence of aneuploidy and congenital structural anomalies were higher in women with low FF compared to the general Dutch obstetric population. Conclusion: Low FF is associated with adverse pregnancy outcomes. The value of FF in the prediction of these outcomes needs to be further established.